2019
DOI: 10.3390/ijms20010176
|View full text |Cite
|
Sign up to set email alerts
|

LGM2605 Reduces Space Radiation-Induced NLRP3 Inflammasome Activation and Damage in In Vitro Lung Vascular Networks

Abstract: Updated measurements of charged particle fluxes during the transit from Earth to Mars as well as on site measurements by Curiosity of Martian surface radiation fluxes identified potential health hazards associated with radiation exposure for human space missions. Designing mitigation strategies of radiation risks to astronauts is critical. We investigated radiation-induced endothelial cell damage and its mitigation by LGM2605, a radioprotector with antioxidant and free radical scavenging properties. We used an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…Similarly, we found that SDG also inhibited LPS-mediated HUVEC injury and apoptosis. This result is also consistent with the result that SDG reduces space radiation-induced damage in lung endothelial cell injury [24].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, we found that SDG also inhibited LPS-mediated HUVEC injury and apoptosis. This result is also consistent with the result that SDG reduces space radiation-induced damage in lung endothelial cell injury [24].…”
Section: Discussionsupporting
confidence: 92%
“…To assess the effects of prolonged spaceflight-like conditions on central nervous system (CNS) health following exposure, 6-month-old female C57BL/6J mice were either irradiated with low-dose γ-ray irradiation (0.04 Gy, LDR), hindlimb unloaded (HLU) or a combination of the two (HLU+LDR) for 21 days, followed by a 4-month readaptation period (Figure 1A). While the LDR γ-ray irradiation used does not recapitulate the entire space radiation spectrum, it constitutes a significant fraction and poses a hazard to astronauts’ health [15].…”
Section: Resultsmentioning
confidence: 99%
“…However, secondary particles produced by the interaction of SPE protons and heavy-charged GCR particles with the spacecraft structure include γ-rays and x-rays [3]. These radiation sources can also deliver a significant fraction of the total mission dose and pose a hazard to astronauts’ health [15]. For chronic irradiation exposure, we used flood sources consisting of plastic sheets embedded with the isotope 57 Co that emits medium energy (122 and 136 keV) γ-rays.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the NLPR3 inflammasome has been reported to directly induce endothelial dysfunction (Zhang et al, 2015;Erdei et al, 2018;Koka et al, 2019). A recent study showed that inhibition of radiation-induced NLRP3 inflammasome activation by LGM2605, an antioxidant and free radical scavenger, alleviated vascular damage (Chatterjee et al, 2019). Inhibitors of HMGB1 or caspase-1 significantly ameliorated endothelium-associated vasodilation in poloxamer 407 (P-407)treated Nlrp3 +/+ mice (Zhang et al, 2015).…”
Section: Nlrp3 Inflammasome In Radiation-induced Atherosclerosismentioning
confidence: 99%